The Impact of coskewness and cokurtosis as augmentation factors in modeling colombian electricity price returns (2022)
This paper explores the empirical validity of an augmented volume model for Colombian electricity price returns (in the present study, the definition of returns is simply the “rate of change” of observed prices for different periods). Of particular interest is the impact of coskewness and cokurtosis when modeling Colombian electricity price returns. We found that coskewness as an augmentation factor is highly significant and should be considered when modeling Colombian electricity price returns. The results obtained for coskewness as an augmentation factor in a volume model are consistent when using either an Ordinary Least Square (OLS) and Generalized Method of Moments (GMM) specification for the data employed. On the other hand, the effect of cokurtosis is highly irrelevant and not significant in most cases under the proposed specification.